Problematika Penerapan Manajemen Pendidikan Di Lembaga Pendidikan Islam - Fathih, Muhammad Amin; Muhlis , Nur Khozim (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
Islamic educational institutions are known as the oldest educational institutions in Indonesia, but in terms of quality and managerial aspects, Islamic educational institutions are still secondary. This is inseparable from the many challenges and problems of managerial inadequacy that exist in some Islamic educational institutions. Artikel aims to examine the problem of implementing management in Islamic educational institutions. The method used in this article is a literature study by reviewing some literature related to the theme that the author will study. The results show that one of the management problems in Islamic educational institutions is the lack of Islamic education managers in meeting the needs and expectations of stakeholders, then there are still authoritarian and centralistic leadership practices that apply in some Islamic educational institutions, the existence of a dichotomy in Islamic educational institutions that causes the emergence of two groupings to scientists, the lack of competent human resources, especially in its managerial aspect and the strength of several Islamic educational institutions in maintaining the values of local wisdom, so it also has an impact on the unwillingness of Islamic education to innovate in accordance with the times.